2022-RA-687-ESGO ARTISTRY-7: phase 3, multicenter study of nemvaleukin alfa plus pembrolizumab versus chemotherapy in patients with platinum-resistant epithelial ovarian, fallopian tube, or primary peritoneal cancer (GOG-3063; ENGOT-OV68). (20th October 2022) - Herzog, Thomas J; Moore, Kathleen; Konstantinopoulos, Panagiotis A; Gilbert, Lucy; Hays, John L; Monk, Bradley J; O'Malley, David M; Barlin, Joyce N; Graham, Julie R; Desai, Monali; Wang, Yan; Du, Yangchun; et al.
Abstract : Introduction/Background: ARTISTRY-7 will evaluate the novel engineered cytokine nemvaleukin alfa (nemvaleukin, ALKS 4230) in patients with gynaecological cancers. Epithelial ovarian cancer (EOC) is the 7th most common cause of cancer mortality in women, and many patients become resistant/refractory to frontline platinum-based chemotherapy. Nemvaleukin was designed to selectively bind to the intermediate-affinity interleukin-2 receptor, preferentially activating antitumour CD8 + T and NK cells with minimal regulatory T cell expansion. This selectivity may provide enhanced tumour killing and improved safety/tolerability versus high-dose interleukin-2. In ARTISTRY-1, responses were observed with nemvaleukin+pembrolizumab in 4 patients with platinum-resistant ovarian cancer: 2 complete responses (1 in a patient with 5 prior lines of therapy), and 2 partial responses. Methodology: ARTISTRY-7 (NCT05092360 ) is an ongoing, currently enrolling phase 3, multicentre, randomised study of nemvaleukin and/or pembrolizumab versus chemotherapy. Eligible patients are women (≥18 years) with histologically confirmed EOC (high-grade serous, endometrioid, clear cell), fallopian tube cancer, or primary peritoneal cancer. Patients must have had ≥1 prior line of systemic therapy (platinum-sensitive setting), ≤5 prior lines (platinum-resistant setting), and prior bevacizumab, with radiographic progression on most recent therapy. Patients with primary platinum-refractory disease (progression on first-line platinum therapy) or primary platinum resistance (progression <3 months after first-line platinum therapy completion) are excluded. Approximately 376 patients are being randomised (3:1:1:3) to receive nemvaleukin 6 μg/kg intravenously (days 1–5) + pembrolizumab 200 mg intravenously (day 1) of each 21-day cycle, pembrolizumab or nemvaleukin monotherapy, or chemotherapy, and stratified by PD-L1 status, histologic subtype, and chemotherapy (paclitaxel vs others). Patients will continue treatment until disease progression or intolerable toxicity (maximum 35 pembrolizumab cycles; nemvaleukin can be continued). Primary endpoint: investigator-assessed progression-free survival (RECIST v1.1) in the nemvaleukin+pembrolizumab versus chemotherapy arms. Secondary/exploratory endpoints include overall survival, other anti-tumour measures, safety, health-related quality of life, and pharmacokinetic/pharmacodynamic effects. Results: not applicable Conclusion: not applicable